Studying the transformations of contemporary residential buildings in Lattakia - Alshaikh, Ramzi (Latakia University Journal -Engineering Sciences Series, 2019)
لمسكن أحد أهم عناصر الإطار أو المحيط العمراني. نتج عن تـفاعل العديد من العوامل التي ساهمت في تشكيله سواء فيما يتعلق بخصائصه كعمره وطرازه ومكانه في المدينة وسعته أو في ما يتعلق بواقع الظروف المحيطة التي تنشأ فيها ,لذلك فإن حالة أي مسكن ذي طراز معماري تستمد قيمة التاريخية والجمالية بالإضافة إلى دوره الهام في تلبية لاحتياجات الساكنين وتأمين الراحة لهم. يقدم البحث دراسة تحليلية لواقع السكن المعاصر وتغيراته في مدينة اللاذقية خلال الفترة الزمنية بين (1921-2014) لرصد أهم التحولات التي طرأت عليه نتيجة الظروف السياسية والاقتصادية والاجتماعية على المستوى المعماري (المسكن ) والعمراني ( المجمعات السكنية). خلص البحث إلى مجموعة من الجوانب المعمارية التي تغيرت في المبنى السكني في مدينة اللاذقية ,وحددت أهم الأسباب التي أدت إلى التغير في هذا الجانب . Housing is an important element of architectural surrounding, that appears to be an outcome of the interaction of a number of factors whether regarding its age, model, location, and area. So any building is valued by its aesthetic historic value as well as its capacity to satisfy the needs and comfort of its inhabitants. The research presents an analytical study of the reality of contemporary housing and its changes in the city of Latakia during the period 1921-2014, to register the most important transformations that have occurred as a result of political, economic and social conditions on the architectural level (housing) and urban level (residential complexes). The research has sum up a set of architectural aspects that have changed in the design of buildings in Latakia , along with the most important reasons causing this change.